1992
DOI: 10.1002/jcp.1041520209
|View full text |Cite
|
Sign up to set email alerts
|

Changes in responsiveness of rat tracheal epithelial cells to transforming growth factor‐β1 with time in culture

Abstract: Primary rat tracheal epithelial (RTE) cell cultures have previously been shown to be highly sensitive to growth inhibition by transforming growth factor-beta 1 (TGF beta 1) when treated within 1-2 days after plating. The purpose of the present studies was to examine the effects of TGF beta 1 on the growth of RTE cells as a function of time in culture. We found that the sensitivity of RTE cells to growth inhibition by TGF beta 1 decreased dramatically as the cultures aged. The IC50 for inhibition of colony form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Treatment with 10 pM TGF[3~ for 24 h resulted in a 40% inhibition of DNA synthesis. This is similar to the result of Rundhaug et al (1992) who reported that in 5-d-old cultures of RTE cells grown on plastic, TGF[3~ inhibited DNA synthesis with an ICso of 3-4 pM. Thus, RTE cells are sensitive to TGFl3~-induced growth arrest whether cultured submerged on plastic or at an ALI on a collagen gel.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Treatment with 10 pM TGF[3~ for 24 h resulted in a 40% inhibition of DNA synthesis. This is similar to the result of Rundhaug et al (1992) who reported that in 5-d-old cultures of RTE cells grown on plastic, TGF[3~ inhibited DNA synthesis with an ICso of 3-4 pM. Thus, RTE cells are sensitive to TGFl3~-induced growth arrest whether cultured submerged on plastic or at an ALI on a collagen gel.…”
supporting
confidence: 91%
“…Previous studies have demonstrated that primary-RTE cells in monolayer culture produce and respond to TGFI3s (Rundhaug et al, 1992;Rundhaug and Nettesheim, 1993). In these experiments, TGFI3s inhibited DNA synthesis and cell growth, and also increased terminal (squamous) differentiation (Rundhaug et al, 1992). TGF]3~ also induced squamous differentiation in cultures of human (Masui et al, 1986) and rabbit (Jetten et ah, 1986) tracheobronchial cells.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Cells were then plated at the indicated densities in 2 mliwell in 12-well dishes (secondary cultures). Since we knew the replating efficiency of RTE cells decreases with time in primary culture Rundhaug et al, 1992), the seeding density of the replated cells was adjusted according to the age of the primaries in order to obtain a minimum of 1-2 colonieskulture in the controls. The day after replating, the media were changed (1 ml/well) and antibodiesiIgGs added.…”
Section: Colony-forming Efficiencymentioning
confidence: 99%